Practical Channel Hydraulics, 2nd edition : Roughness, Conveyance and Afflux /: Roughness, Conveyance and Afflux. (2018) - Knight, Donald W; Hazlewood, Caroline; Lamb, Rob; Samuels, Paul G; Shiono, Koji
No abstract available